2008
DOI: 10.1007/s11096-008-9242-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-initiated general practitioner referral of patients with suboptimal asthma management

Abstract: The results suggest that community pharmacists are ideally placed to identify patients with suboptimal asthma management and refer such patients for a review by their GP. This type of collaborative intervention can significantly improve self-reported asthma control and asthma-related QOL in patients identified as having suboptimal management of their asthma. A larger trial is needed to confirm the effects are real and sustained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 24 publications
2
67
0
Order By: Relevance
“…However, since those on preventer therapy would need regular prescriptions, we assume that there would have been frequent opportunities to intervene, either by the GP or pharmacist. A recent publication has emphasised how effective intervention from healthcare professionals can be, including improving quality of life, when an inadequate level of therapy relative to disease severity is noticed 27. Bereznicki et al show strong evidence that patients are prepared to change therapeutic practice under good professional guidance 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since those on preventer therapy would need regular prescriptions, we assume that there would have been frequent opportunities to intervene, either by the GP or pharmacist. A recent publication has emphasised how effective intervention from healthcare professionals can be, including improving quality of life, when an inadequate level of therapy relative to disease severity is noticed 27. Bereznicki et al show strong evidence that patients are prepared to change therapeutic practice under good professional guidance 27.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication has emphasised how effective intervention from healthcare professionals can be, including improving quality of life, when an inadequate level of therapy relative to disease severity is noticed 27. Bereznicki et al show strong evidence that patients are prepared to change therapeutic practice under good professional guidance 27. This contrasts with published evidence that physicians have found it challenging to adhere to NAC guidelines, suggesting perceived limitations to such a regimented “one size fits all” approach.…”
Section: Discussionmentioning
confidence: 99%
“…patients with possible uncontrolled asthma were identified, provided written information and a doctor referral, no significant change was observed in the asthma knowledge score [32,47]. Our instrument can thus be used in the community setting to assess effectiveness of education programs.…”
Section: "I Think When You've Been An Asthmatic a Long Time Previousmentioning
confidence: 99%
“…It has been demonstrated that community pharmacies are suitable venues to identify patients in need of asthma education, i.e. those with poorly-controlled asthma and those with poor medication adherence identifiable through pharmacy records [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…DM aims to supply new, valuable, and potentially useful information from big databases [19,20]. DM techniques can be used extensively in hospitals, clinics and pharmacies by healthcare providers to give better and more affordable healthcare services to the patients [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%